The dietary impact of the COVID-19 pandemic - Martin O'Connell; Kate Smith; Rebekah Stroud (Institute for Fiscal Studies (IFS), 2021)
The COVID-19 pandemic has led to significant changes in where people work, eat and socialise. We use novel data on the food and non-alcoholic drink purchases from stores, takeaways, restaurants and other outlets to quantify the impact of the pandemic on the diets of a large, representative panel of British households. We find that a substantial and persistent increase in calories consumed at home more than offset reductions in calories eaten out. By May 2020 (towards the end of the UK's first national lockdown), total calories were, on average, 15% above normal levels, and they remained higher than normal for the rest of 2020. All socioeconomic groups increased their calorie purchases, with the largest rises for the highest SES households and the smallest for retired ones. Our findings suggest that the COVID-19 pandemic and the associated changes in people's lifestyles have exacerbated the challenges of improving population diet and reducing obesity levels.
Keywords: D12; I12; 330; obesity; COVID-19; health; diet; nutrition; pandemic